An Approach to Information Retrieval from Construction Images - Aqli Mursadin (Jurnal Teknologi Berkelanjutan, 2012)
Construction images are potentially valuable sources of information. However, there are several problemsrelated to its retrieval mainly relating to understanding of the semantics of the corresponding content. Additionally, theinformation is. very much unstructured in nature. These problems have been solved by the development of conceptsenabling the content to be represented in structured form. The framework proposed for this is described. It is based onthe use of domain-specific concepts to retrieve image content and contextual information to improve contentunderstanding. A mathematical framework is also developed based on a Bayesian approach to make the implementationpossible for construction image classification. This robust framework enables fusion of related domain knowledge withnew information in a versatile manner. An example demonstrates how it is possible to combine information from bothavailable image data and domain knowledge to understand construction image content.